Three new grasshopper species in the Florida Melanoplus Puer Group (Orthoptera: Acrididae: Melanoplinae) - Woller, Derek A. (Zootaxa, 2025)
Three new grasshopper species in the Melanoplus Puer Group sensu lato (Orthoptera: Acrididae: Melanoplinae) are described from Florida, United States, bringing the total number of described species in the group to 27 while the number of species in the Puer Group sensu stricto is increased to nine. 1) M. amphora sp. nov. Woller, Kelly, and Orfinger is described from a relatively small region of southeastern Florida across four counties: Okeechobee, Brevard, Indian, and St. Lucie, with the latter three being along the east coast; 2) M. spiracor sp. nov. Woller and Kelly is described from a small region of southwestern Florida across three counties: Hillsborough, Manatee, and Sarasota, all of which are along the west coast; and 3), M. ferrarius sp. nov. Woller, Kelly, and Orfinger is described from a single location in southeastern Florida within Martin County: Jonathan Dickinson State Park, which is along the east coast. Taxonomic placement of these species is justified based on distinct morphology, primarily of the internal genitalia (especially the shape of the aedeagus), which are sufficiently divergent from conspecifics and consistently unique enough across their known geographic ranges to be considered new species. Comparisons with some geographically close congeneric species in the Puer Group are also provided.